Perancangan Poros Roda Depan Motor Yamah New Jupiter MX 135cc 2014 - Muhamad Mahbub Albuhori; Kardiman Kardiman; Viktor Naubnome (Peneliti.net, 2022)
Currently, motorcycles are a means of transportation that is widely used in Indonesia and even motorcycles are used as a primary need for a company or individual. This is because the price of motorcycles is relatively cheap for most people and also fuel and operational costs are quite affordable. In order for the vehicle to work properly, good components are needed, one of the components is the shaft on the wheels of the vehicle. This shaft serves to support the load of the vehicle itself as well as loads from outside such as, humans or cargo on a motorcycle. The purpose of this study is to find out the diameter that must be used on the front wheel axle of the yamah new jupiter mx 135cc motor. the method used is experimentation. The results of this study obtained the maximum normal voltage value on the shaft with a value of 525 Mpa, a security factor of 1.4, a permissible nprmal voltage of 410.7 Mpa and a shaft diameter used of 11 mm.